The relationship between fall anxiety and fall behaviors in geriatric patients undergoing orthopedic surgery with a history of falling - Altintas, Sibel; Sahiner, Sema; Çelik, Sevim; Karahan, Elif (Pacini Editore, 2025)
Background. Falls in older adults pose significant health risks and have both physical and psychological effects. This condition is an important factor influencing fall anxiety and fall behaviors. Aim. The aim of this study is to examine the relationship between fall anxiety and fall behaviors in geriatric patients who were admitted to the orthopedic ward and underwent orthopedic surgery due to a fall. Method. A cross-sectional correlational study was conducted with 97 patients aged 65 and above in the orthopedic clinic of a state hospital between September 2023 and September 2024. Data were collected through face-to-face surveys using the Patient Identification Form, the International Falls Efficacy Scale, and the Fall Behaviors Scale for Older Adults, and statistical analysis was performed. Results. The average age of the patients was 72.62 +/- 6.52, with 55.7% being male, 76.3% married, 86.6% unemployed, and 40.2% having completed primary school. 76.3% had chronic illnesses, and 75.3% had a history of surgery. 85.6% of the patients reported fall anxiety, and 78.4% had a fall history. High levels of fall anxiety and risk were found, and demographic factors were found to be associated with these behaviors. Conclusions. A strong relationship between fall anxiety and fall risk was observed in older individuals. To reduce this, it is suggested to implement physical activity programs, educational interventions, environmental adjustments, and psychosocial support. Additionally, the need for multidisciplinary research is emphasized.
Keywords: fall behaviors; fall anxiety; geriatrics; fall; fall behaviors; fall anxiety; geriatrics; orthopedic surgery